Gender Analysis of Student Career Self-Efficacy and Implications in Career Guidance Services at State Vocational Schools - Abdullah Pandang; Nur Fadhilah Umar; Akhmad Harum (Universitas Negeri Makassar, 2022)
This study aims to determine the differences in career self-efficacy of female and male students at SMK Negeri Makassar City. The study took a population of high school students in Makassar City, with a sample of 426 students, consisting of 215 girls and 211 boys. The career self-efficacy variable data collection instrument was developed and adapted from the Career Decision Self-Efficacy Scale (CDSE-SF) from Betz, Klein, & Taylor. The results of the study show that there was no significant difference in the career self-efficacy scores of female students and male students at SMK Negeri Makassar City. Significant differences were seen only in the maritime skills program, where female students' self-efficacy was higher than male students. In contrast, in the six skill programs, both sexes showed no significant difference in career self-efficacy.Â